2017
DOI: 10.1080/13696998.2016.1277229
|View full text |Cite
|
Sign up to set email alerts
|

Employment and absenteeism in working-age persons with multiple sclerosis

Abstract: In MS, employment status and absenteeism are negatively affected by disability, cognitive impairment, and fatigue. These findings underscore the need for therapies that prevent disability progression and other symptoms that negatively affect productivity in persons with MS to enable them to persist in the workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 37 publications
7
47
0
Order By: Relevance
“…It has been suggested that the HRQOL of people with MS deteriorates when they leave the workforce, 16 and, therefore, employment has been suggested as a potential public health intervention for people with MS. 17 Exploring attributes or dimensions of HUI3 associated with employment status, we found that three (cognition impairment, physical disability [mobility impairment], and pain/discomfort) of eight attributes of HUI3 were strongly associated with not working due to MS. The present findings concur with previous studies that have found a higher likelihood of unemployment among people with MS who reported cognition impairment, 38,41,47 physical disability, [38][39][40][41]45 and pain. 48 As such, interventions targeting these specific HRQOL attributes may contribute to improving the overall quality of life of people with MS and subsequently their work productivity.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It has been suggested that the HRQOL of people with MS deteriorates when they leave the workforce, 16 and, therefore, employment has been suggested as a potential public health intervention for people with MS. 17 Exploring attributes or dimensions of HUI3 associated with employment status, we found that three (cognition impairment, physical disability [mobility impairment], and pain/discomfort) of eight attributes of HUI3 were strongly associated with not working due to MS. The present findings concur with previous studies that have found a higher likelihood of unemployment among people with MS who reported cognition impairment, 38,41,47 physical disability, [38][39][40][41]45 and pain. 48 As such, interventions targeting these specific HRQOL attributes may contribute to improving the overall quality of life of people with MS and subsequently their work productivity.…”
Section: Discussionsupporting
confidence: 93%
“…As expected and consistent with previous studies, 9,[38][39][40][41] we found that sociodemographic factors, including increasing age and higher education attainment, were associated with unemployment in people with MS. However, the sex of the person with MS was not associated with unemployment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moderate to severe cognitive impairment, fatigue, and hand function problems were associated with both disability and absenteeism. 22 Of adults 65 years or older, 15% of patients without MS reported using an assistive device, whereas 81% of patients with MS required an assistive device in the NARCOMS cohort, a 6-fold difference. 23,24 Long-term follow-up studies of patients on platform agents reveal the risks of undertreatment An extension of the pivotal glatiramer acetate trial found that of patients who were maintained on treatment for an average of 13.6 years, 35% were likely to develop secondary progressive disease.…”
Section: Ms Is Rarely Benign Over the Long Term When Dysfunction Is Cmentioning
confidence: 87%
“…The worldwide unemployment rates of people with MS range from 30% to 43% within 11 to 19 years of disease onset 5,6,7,8,9 and work availability decreases from 82% to 8% 10 . Having MS more than triples the chance of losing the current job 11 , and simply publicly disclosing the MS diagnosis has a major negative impact on the chance of becoming employed or having a remunerated activity 3,12 .…”
Section: Introductionmentioning
confidence: 99%